FINANCIAL MANAGEMENT MECHANISMS AS A FACTOR FOR INCREASING THE COMPETITIVENESS OF ENTERPRISES IN A CRISIS PERIOD (Development Service Industry Management, 2025)
The article examines the theoretical and practical aspects of financial management mechanisms in the context of the modern economy's crisis challenges. It is demonstrated that financial management plays a crucial role in ensuring the sustainability of enterprises, shaping their competitiveness, and determining strategic development directions. Particular attention is paid to the analysis of tools and methods that allow enterprises to adapt to changes in the external environment, maintain liquidity, optimize costs, and attract additional sources of financing. The impact of crisis processes on the transformation of traditional approaches to financial management is examined, and the need to adopt new models that prioritize flexibility and a long-term perspective is demonstrated. It is established that in the context of military operations and the post-war recovery of the Ukrainian economy, financial management acquires special importance. Enterprises are compelled to adopt non-traditional approaches to financial management, specifically by more widely applying digital technologies, utilizing innovative financial instruments, and enhancing their collaboration with investors and donors. The role of the state and international financial organizations in supporting businesses is emphasized, which opens up new prospects for implementing public-private partnerships and creating favorable conditions for the recovery of the national economy. The importance of risk management mechanisms, diversification of financial flows, and strategic planning as tools for strengthening the competitive positions of enterprises is outlined. It is concluded that the future development of financial management in Ukraine will depend on the ability to integrate classical management tools with innovative approaches that consider the realities of the crisis and post-crisis environment. Financial management mechanisms are considered a universal tool capable of simultaneously solving the tasks of adapting business to crisis conditions, forming new competitive advantages, and ensuring the economic stability of the state in a global context.
Keywords: financial management; enterprise competitiveness; crisis management; post-war recovery; financial instruments